ANALISIS MANAJEMEN RISIKO STUDI KASUS : UNIT PELAKSANA TEKNIS BALAI PENGUJIAN DAN LABORATORIUM LINGKUNGAN HIDUP BADAN LINGKUNGAN HIDUP PROVINSI JAWA TENGAH - Anggi Ajie Permana; Winardi Dwi Nugraha; Mochtar Hadiwidodo (Jurnal Teknik Lingkungan, 2013)
AbstrakData from the Ministry of Manpower and Transmigration mention in 2009 there have been 54,398 cases of occupational accidents in Indonesia. Working in a chemical laboratory, as well as working in the chemical industry, mining, and construction, contain risks include risks of safety (Imamkhasani, 1990). This study intend to determine the hazards that exist in the laboratory, perform risk assessments and control measures are appropriate. Hazard identification is done by reviewing aspects of human, environmental, process, system of manpower and equipment. Accident risk assessment carried out degan method of semi-quantitative analysis. The results of this study concluded that BPL2H Central Java province has 37 of hazard in all its activities. Risks in the Central Java BPL2H of research results are acceptable or low risk so the control is only carried out by reducing the intensity of activities that pose a risk to a minimum.